2001
DOI: 10.1136/heart.86.3.336
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 1 receptor antagonist gene polymorphism and restenosis after coronary angioplasty

Abstract: Background-Percutaneous transluminal coronary angioplasty (PTCA) is limited by the recurrence of luminal stenosis, which occurs in up to 50% of procedures. It has been shown that patient specific factors, perhaps genes, contribute to this process. Objective-To determine whether completion of healing after PTCA is part of an acute self limiting inflammatory process and whether polymorphism at important inflammatory gene loci might determine susceptibility to restenosis after PTCA. Design-DNA samples were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 28 publications
1
31
0
1
Order By: Relevance
“…This finding substantiates previous reports of slower progression of restenosis after coronary angioplasty in individuals carrying the 2-repeat allele. [43][44][45] Others have shown that systemic levels of IL-1Ra are increased in carriers of the 2-repeat allele. 46 Hence, the polymorphism of IL-1Ra can alter the baseline balance between IL-1Ra and IL-1β and increase the IL-1Ra :IL-1β ratio.…”
Section: Discussionmentioning
confidence: 99%
“…This finding substantiates previous reports of slower progression of restenosis after coronary angioplasty in individuals carrying the 2-repeat allele. [43][44][45] Others have shown that systemic levels of IL-1Ra are increased in carriers of the 2-repeat allele. 46 Hence, the polymorphism of IL-1Ra can alter the baseline balance between IL-1Ra and IL-1β and increase the IL-1Ra :IL-1β ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Indications for coronary arteriography in our clinic are based on guidelines for coronary angiography 14 . According to coronary angiography results 12,15 participants who presented ≥ 70 % stenoses in at least one of the major coronary arteries were considered as CAD (n= 257) and the remainders who presented ≤ 30 % stenosis were accepted in the normal group (n= 170). CAD group was divided into two subgroups: SVD (only one coronary artery stenosis; n= 91) and Multiple Vessel Disease (MVD; more than one coronary artery stenosis; n= 166).…”
Section: Methods Subjectsmentioning
confidence: 99%
“…Furthermore, it has been reported that IL1RN 2 allele is significantly associated with CAD in the Type 2 diabetes patients 11 . Also, IL1RN 2 allele has a protective effect on restenosis after PTCA 12 and an association between IL1RN 2 and carotid atherosclerosis was reported 22 . It was also reported that future Myocardial Infarction risk was increased with IL1RN 2 allele and high CRP levels in young patients 23 .…”
Section: Discussionmentioning
confidence: 99%
“…IL-1 is a strong contributor to the development of restenosis (5,15) through induction and nuclear translocation of NF-B (23) and increased expression of platelet-derived growth factor and fibroblast growth factor (FGF) (9), and, most notably, IL-1␣ can recruit and activate macrophages, which are the richest cellular source of growth factors in the body (4). Indeed, there is a direct correlation between inflammatory cell infiltration and neointimal formation at the site of vascular intervention (18).…”
mentioning
confidence: 99%